2007
DOI: 10.1370/afm.693
|View full text |Cite
|
Sign up to set email alerts
|

Time to Ban Direct-to-Consumer Prescription Drug Marketing

Abstract: To read or post commentaries in response to this article, see it online at http://www.annfammed.org/cgi/current/full/5/2/101.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 21 publications
0
36
0
1
Order By: Relevance
“…1 Opponents of DTCA argue that it leads to overdiagnosis, unnecessary and inappropriate prescribing, more adverse drug reactions, and increased healthcare costs. [2][3][4] Proponents, on the other hand, maintain that it raises public awareness of underdiagnosed diseases and leads to appropriate increases in diagnostic testing and treatment. 5 Thus far, the limited evidence-of varying methodological quality-on the effects of DTCA is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…1 Opponents of DTCA argue that it leads to overdiagnosis, unnecessary and inappropriate prescribing, more adverse drug reactions, and increased healthcare costs. [2][3][4] Proponents, on the other hand, maintain that it raises public awareness of underdiagnosed diseases and leads to appropriate increases in diagnostic testing and treatment. 5 Thus far, the limited evidence-of varying methodological quality-on the effects of DTCA is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…1,6 Second, they may avert underuse of effective disease treatments, and potentially increase medication adherence. 1,6,7 Finally, they may strengthen patients' relationships with their physicians.…”
mentioning
confidence: 99%
“…1,6 Second, they may avert underuse of effective disease treatments, and potentially increase medication adherence. 1,6,7 Finally, they may strengthen patients' relationships with their physicians. 1,4 Surveys conducted by the FDA in 2004 found that most surveyed physicians felt that DTC advertising made their patients more aware of treatments and feel more engaged in their own health care.…”
mentioning
confidence: 99%
See 2 more Smart Citations